High thermoelectric performance of polycrystalline In4Se3−δ(CuI)x: synergistic effects of the Se-deficiency and CuI-doping12. Issue 12 (18th October 2016) - Chen, Yan-Chun; Lin, Hua; Wu, Li-Ming
Abstract : Synergistic effect of Se-deficiency and CuI-doping significantly enhances the thermoelectric figure-of-merit of the n-type polycrystalline In4 Se3 -based materials via improving the power factor. With In4 Se2.95 (CuI)0.01, ZT = 1.34 at 723 K, the highest value obtained for Pb-free polycrystalline In4 Se3 -based materials to date. Abstract : Polycrystalline n-type In4 Se3 -based materials are established and promising mid-temperature range thermoelectric materials. Herein, we report that synergistic effects of a Se-deficiency and CuI-doping significantly improve the thermoelectric properties of CuI-doped In4 Se3− δ materials via increasing the power factor (PF), an increase of up to 105%, and enhancing the figure-of-merit ( ZT ), by about 80%, compared to the undoped ones. The CuI-doping ( x ) significantly lowers the electrical resistivity and enhances the power factor (PF); and the PF increases with increase of x . But the maximum solubility of the CuI-dopant ( x m ) is restricted by the amount of the Se-deficiency ( δ ), and it closely approaches the δ in the form of x m < δ . Thus, the greater the δ, the greater the PF. On the other hand, the greater the Se-deficiency, the more Cu that will occupy the intercalation sites, which increases the atom packing density and thus indispensably increases the thermal conductivity ( κ ); and consequently the lower the δ, the lower the κ . Such a synergistic effect ensures a balance between improving the PF and lowering the κ, so as to give rise to a considerable ZT enhancement. For example, In4 Se2.70 (CuI)0.2 and In4 Se2.50 (CuI)0.3 provide a ZT max of 1.20 and 1.08, respectively, which are about 80 and 66% enhanced in comparison with the un-doped ones. Especially, a ZT max = 1.34 at 723 K is obtained for In4 Se2.95 (CuI)0.01, representing the highest value obtained for Pb-free polycrystalline In4 Se3 -based materials to date. This insight offers guidance for further studies on these and related TE materials.